PERBANDINGAN EFEK DIURETIK EKSTRAK ETANOL DAUN PEPAYA (CARICA PAPAYA L.) DENGAN FUROSEMID PADA TIKUS PUTIH JANTAN GALUR WISTAR - MERY MARLINA HSB; ILHAM HARIAJI; M. BIOMED; ARIL RIZALDI (LP2MTBM MAKARIOZ, 2022)
Hypertension is still one of the deadliest diseases in Indonesia. According to the Minister of Health, hypertension is the number 3 cause of death after stroke and tuberculosis, which reached 6.7%. Diuretics are drugs that increase the flow rate of urine, but also function to increase the speed of excretion of sodium (natriuresis) and amnion that come out with urine. This study used a posttest with a control group design. Rats were divided into 4 groups with group 1 with Aquadest, group 2 with 30 mg Furosemide, group 3 with papaya leaf extract I dose 60 mg and dose II papaya leaf extract 90 mg. Data will be analyzed by Kruskal-wallis and post Hoc Mann-Whitney. The result of this research There was a relationship between administration of papaya leaf extract with a diuretic effect in white Wistar rats, with the Kruskal-wallis test p values <0.05.